Estimation of the Minimum Number of Replication Origins Per Chromosome in any Organism - da Silva, Marcelo S. [UNESP] (2020)
Eukaryote nuclear genomes predominantly replicate through multiple replication origins. The number of replication origins activated per chromosome during the S-phase duration may vary according to many factors, but the predominant one is replication stress. Several studies have applied different approaches to estimate the number and map the positions of the replication origins in various organisms. However, without a parameter to restrict the minimum of necessary origins, less sensitive techniques may suggest conflicting results. The estimation of the minimum number of replication origins (MO) per chromosome is an innovative method that allows the establishment of a threshold, which serves as a parameter for genomic approaches that map origins. For this, the MO can be easily obtained through a formula that requires as parameters: chromosome size, S-phase duration, and replication rate. The chromosome size for any organism can be acquired in genomic databanks (such as NCBI), the S-phase duration can be estimated by monitoring DNA replication, and the replication rate is obtained through the DNA combing approach. The estimation of MO is a simple, quick, and easy method that provides a new methodological framework to assist studies of mapping replication origins in any organism.